Asymptomatic Filariasis in Loreto - Pecse, Hugo (1958)
This note is primarily intended to strengthen the priority of clinical and epidemiological studies of Manuel Marín Barrantes; and merely "preliminary" nature of this note clearly states not to invade the originality of its thesis.